2020
DOI: 10.3389/fmicb.2020.01811
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Viability Treatment Essential for Accurate Droplet Digital PCR Enumeration of Probiotics

Abstract: Improvements offered by viability droplet digital PCR (v-ddPCR) include increased precision, specificity and decreased time to results making for an attractive alternative method to traditional plate count enumeration of probiotic products. A major hurdle faced in v-ddPCR, however, is distinguishing between live and dead cells. The objective of this study was to evaluate a combination of PMA and EMA (PE51) for viability treatment of freeze-dried probiotic powders. Lactobacillus acidophilus La-14 and Bifidobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…These assays can be further optimized and validated as quantitative methods for viable count determination in qPCR or droplet digital PCR based methods ( Hansen et al, 2018 , 2020 ; Shehata and Newmaster, 2021 ). This will require the use of viability dyes to distinguish live versus dead cells, and previous work showed that viability dyes must be optimized for each assay ( Kiefer et al, 2020 ). After generating standard curves, colony forming units (CFUs) can be interpolated based on Cq values.…”
Section: Discussionmentioning
confidence: 99%
“…These assays can be further optimized and validated as quantitative methods for viable count determination in qPCR or droplet digital PCR based methods ( Hansen et al, 2018 , 2020 ; Shehata and Newmaster, 2021 ). This will require the use of viability dyes to distinguish live versus dead cells, and previous work showed that viability dyes must be optimized for each assay ( Kiefer et al, 2020 ). After generating standard curves, colony forming units (CFUs) can be interpolated based on Cq values.…”
Section: Discussionmentioning
confidence: 99%
“…Culture-dependent methods, where plate count enumeration is the most prevalent, have for long been the standard for viability measurement of probiotic cultures and products (Lahtinen et al, 2006;Davis, 2014;Hansen et al, 2020;Kiefer et al, 2020). They are uncomplicated to perform but laborious and require media and conditions that are well adapted to the strain of interest (Davis, 2014).…”
Section: Culture-dependent Methods For Viability Assessmentmentioning
confidence: 99%
“…Factors such as oxygen tolerance, antibiotic susceptibility, and nutritional preferences must be considered when choosing and designing suitable media and cultivation conditions. Thus, although sometimes possible with antibiotics, it can be difficult to separate a mixture of two or several strains with highly similar growth requirements (Jackson et al, 2002;Hansen et al, 2018;Vinderola et al, 2019;Kiefer et al, 2020).…”
Section: Culture-dependent Methods For Viability Assessmentmentioning
confidence: 99%
See 2 more Smart Citations